Value of information through options contract under disruption risk. (January 2017) - Köle, Hüseyin; Bakal, Ismail Serdar
Highlights: We model the replenishment strategy of a dual-sourcing buyer under disruption risk. We examine the benefits of an options contract with a reliable supplier. We consider three levels of information regarding the timing of option-exercise. We analytically characterize settings where the buyer chooses to single-source. The value of a flexible supplier increases as supply/demand uncertainty increases. Abstract: In this study, we consider the replenishment strategy of a buyer with two suppliers. Since its regular supplier is prone to disruptions, the buyer utilizes an options contract with a more expensive but perfectly reliable supply option. We introduce three models depending on the level of information available when the options from the reliable supplier are exercised: (i) Full information (both supply and demand information), (ii) partial information (only supply information), and (iii) no information. We derive the optimal replenishment strategy of the buyer in each of these models and characterize the conditions under which the reliable supplier is utilized. Through both analytical and numerical studies, we investigate the effectiveness of an options contract under different levels of information.